The impact of carbon disclosure mandates on emissions and financial operating performance - Benedikt Downar; Jürgen Ernstberger; Stefan Reichelstein; Sebastian Schwenen; Aleksandar Zaklan (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We examine whether a disclosure mandate for greenhouse gas emissions creates stakeholder pressure for firms to subsequently reduce their emissions. For UK-incorporated listed firms such a mandate was adopted in 2013. Using a difference-in-differences design, we find that firms affected by the mandate reduced their emissions - depending on the specification - by an incremental 14-18% relative to a control group. This reduction was accompanied by an average 9% increase in production costs. At the same time, the treated firms were able to increase their sales by an almost compensating amount. Taken together, our findings provide no indication that the disclosure requirement led to a significant deterioration in the financial operating performance of the treated firms, despite the significant carbon footprint reduction following the disclosure mandate.
Keywords: Q28; Q40; M41; M48; 330; disclosureof non-financial information; mandatory disclosure; greenhouse gas emissions; real effects